A Clinical Case of Successful Surgical Correction of Tetralogy of Fallot by Using the Right Atrial Appendage as a Neopulmonary Valve - Bakhytzhan Nurkeyev; Shukhrat Marassulov; Yerbol Aldabergenov; Akkerbez Adilbekova; Saniya Murzabayeva; Elmira Kuandykova; Asiya Akhmoldaeva (National Scientific Medical Center, 2024)
Tetralogy of Fallot (TOF) is one of the common cardiac malformation with depletion of the pulmonary circulation. In the long term, preservation of neopulmonary bicuspid valve function in Tetralogy of Fallot has a key value in pediatric cardiac surgery. In 2019, a cardiac surgeon from Iran, Amirghofran A, introduced a completely new method of forming a neopulmonary valve from the appendage of the right atrium. Previously, many attempts have been made to preserve the pulmonary valve using both autologous and foreign tissue, but the results have been disappointing. the usage of the right atrial appendage as a bicuspid valve in the pulmonary position is an alternative method for correction of Tetralogy of Fallot with deformed, hypoplastic and aplasic pulmonary valve. However, more follow-up is required to obtain data that are more reliable.